A review of best food safety practices: International experiences and lessons for Bangladesh - Saak, Alexander E. (International Food Policy Research Institute, 2019)
The goal of this report is to identify best food safety practices that can inform policy makers in Bangladesh and other developing countries by examining and synthesizing experiences in food safety systems and regulation as well as producer and consumer behavior in low, middle, and high income countries. We begin by presenting the general objectives and principles of food safety regulation in countries with mature food safety systems. Then we review government food safety regulatory systems in Denmark and the U.S. to illustrate different approaches to organizing the implementation of food safety regulation. The food safety systems of both of these countries were updated within the past 20 years (Denmark in 1997 and the U.S. in 2011), and as a result the two systems incorporate modern best practices in food safety. The recent changes to U.S. food safety law are described in depth, as an example of a country updating a food safety system that was developed over 80 years ago based on modern principles. We conclude by summarizing the best practices and consider their potential to improve food safety in an emerging economy such as Bangladesh.